PECULIARITIES OF MOVEMENTS USED IN THE PHYSICAL REHABILITATION OF PEOPLE WITH DISABILITIES (American Journal of Pedagogical and Educational Research, 2025)
The article provides a methodological basis for the effective organization of this activity, the specific features of the use of auxiliary devices in the restoration and development of the physical abilities of people with disabilities. The author considers the main goal of physical education of people with disabilities to be improving the functional state of a person, restoring or developing movement, and ensuring social adaptation.